An Application of GARCH Models in Detecting Systematic Bias in Options Pricing and Determining Arbitrage in Options - Dash, Mihir; Dagha, Jay H.; Sharma, Pooja; Singhal, Rashmi (Pontificia Universidad Católica del Perú. CENTRUM, 2012)
Derivatives have become widely accepted as tools for hedging and risk-management, as well as speculation to some extent. A more recent trend has been gaining ground, namely, arbitrage in derivatives.
Keywords: Black-Scholes model; GARCH; Arbitrage; Derivatives; Hedging; Overpricing; Speculation; Volatility; https://purl.org/pe-repo/ocde/ford#5.02.04